SARS-CoV-2 Variant-Specific Antibodies in Vaccinated Inflammatory Bowel Disease Patients - Eva Ulla Lorentzen; Richard Vollenberg; Rieke Neddermeyer; Michael Schoefbaenker; Eike R. Hrincius; Stephan Ludwig; Phil-Robin Tepasse; Joachim Ewald Kuehn (Vaccines, 2025)
Background/Objectives: Patients suffering from inflammatory bowel diseases (IBDs) undergoing treatment with anti-TNF antibodies mount a diminished humoral immune response to vaccination against SARS-CoV-2 compared to healthy controls. The characterization of variant-specific immune responses is particularly warranted among immunosuppressed patients, where reduced responses may necessitate further medical interventions. Methods: This pilot study investigated the humoral immune response of vaccinated IBD patients on anti-TNF medication and a comparable group of healthy individuals against the viral variants Alpha, Beta, Gamma, Delta, and Omicron BA.1 and BA.5. While total IgG antibodies targeting the receptor binding site of the spike protein of SARS-CoV-2 were quantified using a chemiluminescence microparticle immunoassay (CMIA), their potential neutralizing capacity was determined using commercial and variant-specific in-house surrogate virus neutralization tests (sVNTs) against a variant-specific in-house VSV-pseudotyped virus neutralization test (pVNT) as the gold standard. Results: Employing variant-specific assays recapitulated the immune escape functions of virus variants. Conspicuously, antibody reactivity against Alpha and Omicron BA.1 and BA.5 was strikingly poor in IBD patient sera post-initial vaccination compared to healthy individuals. A comparison of the diagnostic performance of assays with the pVNT revealed that identification of patients with inadequate humoral responses by CMIA and sVNT may require adjustments to cut-off values and end-point titration of sera. Following adaptation of cut-off values, patient sera exhibited reduced reactivity against all tested variants. The assay panel used substantiated the impact of anti-TNF therapy in IBD patients as to reduced strength, function, and breadth of the immune response to several SARS-CoV-2 variants. The immune response measured following the second vaccination was comparable to the antibody response observed in healthy individuals following the first vaccination. Conclusion: Variant-specific sVNTs and pVNTs have the potential to serve as valuable tools for evaluating the efficacy of adapted vaccines and to inform clinical interventions in the care of immunosuppressed patients. Anti-TNF-treated individuals with antibody levels below the optimized CMIA threshold should be considered for early booster vaccination and/or close immunological monitoring.